Equilibrium and kinetic study and modeling of Cu(II) and Co(II) synergistic biosorption from Cu(II)-Co(II) single and binary mixtures on brown algae C. indica. Issue 1 (March 2015) - Akbari, Masoumeh; Hallajisani, Ahmad; Keshtkar, Ali Reza; Shahbeig, Hossein; Ali Ghorbanian, Sohrab
Highlights: With chemical processing by NaCl, maximum biosorption was investigated. It was found uptake process followed the pseudo-second order expression. Langmuir isotherm fitted better than the others for Cu and Temkin isotherm for Co. In binary system, the extended Freundlich isotherm fitted better than the others. Abstract: Biosorption of Cu(II) and Co(II) ions from aqueous solutions by Cystoseira indicia (C. indica ) biomass was investigated in single metal systems as a function of initial pH, initial biomass concentration and temperature. The optimum biosorption conditions were studied for each metal separately. Three kinetic models (pseudo-first order, pseudo-second order and Weber–Morris intraparticle diffusion rate) were used to correlate the experimental data and the kinetic parameters were determined. The results indicated that biosorption fitted well with the pseudo-second order kinetic model. The thermodynamic parameters were determined at three (25, 35 and 45 °C) different temperatures using the thermodynamics constant of Langmuir. The Δ H ° and Δ G ° values of Cu(II) and Co(II) biosorption on C. indica show endothermic heat of biosorption; higher temperatures favor the process. The experimental data were analyzed using Langmuir, Freundlich and Temkin isotherm models so that, the Langmuir and Temkin isotherm models fit successfully to the Cu(II) and Co(II) experimental data, respectively. Also simultaneous biosorption of Cu(II), Co(II) onto C. indica from binary mixtures was investigated. Equilibrium studies were carried out in binary mixtures in which Cu(II) and Co(II) concentrations were varied between 25 and 300 mg/L, respectively. Results showed that both components of the binary mixture exert a synergistic effect on each other. The best fit for Cu(II)–Co(II) experimental data were provided by the extended-Freundlich isotherm model.